Lack of influence of the Schneiderian membrane in forming new bone apical to implants simultaneously installed with sinus floor elevation: an experimental study in monkeys - Scala, Alessandro [UNESP]; Botticelli, Daniele [UNESP]; Faeda, Rafael Silveira [UNESP]; Rangel, Idelmo Garcia [UNESP]; Oliveira, José Américo de [UNESP]; Lang, Niklaus P. (Wiley-Blackwell, 2012)
Aim: To describe the early healing processes around the implants installed after elevation of the sinus mucosa applying the lateral access technique without the use of grafting material.Material and methods: Immediately after the elevation of the maxillary sinus Schneiderian membrane by the lateral approach in eight monkeys, implants were installed without the use of grafting material. The healing of the tissue around the implants was evaluated after 4, 10, 20 and 30 days. Ground sections were prepared and analyzed histologically.Results: After 4 days of healing, the formation of coagulum and provisional matrix was documented within the elevated area. At 10-day interval, sprouts of woven bone were in continuity with the parent bone, and partly in contact with the implant surface at the base of the augmented area. While bone-to-implant contact increased after 20 and 30 days, the area underneath the Schneiderian membrane appeared reduced in volume and condensed toward the apex of the implants. The sinus mucosa was to some extent collapsed onto the implant surface and on the newly formed bone.Conclusions: The void initially occupied by the coagulum after sinus membrane elevation shrank substantially during the observation period. A lack of influence of the Schneiderian membrane in bone formation apical to implants was documented in the early phase of healing.
Keywords: animal study; bone formation; implant dentistry; lateral approach; osseointegration; Schneiderian membrane; sinus floor elevation